Leadership and management practices in enhancing educational services: a case study of a faith-based school in Madiun, East Java, Indonesia - Wahyuni, Atik; Riyadi, Riyadi; Karsono, Karsono (Universitas Ahmad Dahlan, 2024)
Leadership and management are pivotal in enhancing service quality within faith-based educational institutions. This study examines how leadership and management synergy improves school services in a faith-based educational institution in Madiun, East Java. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The findings reveal that effective leadership fosters collaboration among stakeholders, optimizes resource allocation, and implements innovative educational strategies that enhance interdisciplinary learning and student engagement. The school also emphasizes character education to support holistic student development, integrates digital tools to modernize teaching practices, and adopts adaptive assessment strategies to ensure comprehensive evaluation of student competencies. Furthermore, the dual governance system, blending religious identity with national educational standards, highlights the importance of adaptive leadership in maintaining institutional balance. Challenges identified include disparities in resource allocation, scalability of character development programs, and uneven implementation of technology integration. These findings offer a framework for other faith-based institutions to enhance service quality by prioritizing collaborative leadership, professional development, and sustainable management practices. This research contributes valuable insights into effective leadership models in the context of faith-based education and provides actionable recommendations for achieving long-term excellence in service delivery.